DECISION MAKING IN STOCK MARKET USING FUZZY SOFT MATRIX - Mrs. Namrata N. Nadgauda (1), Prof. Dr. Dharmendra Saxena (2) (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
In this paper, we study matrix representation of fuzzy soft sets, complement of fuzzy soft sets, product of fuzzy soft matrices, and application of fuzzy soft matrices in stock market. In addition, we present a new method (max-min-mean) based on the fuzzy reference function instead of the max-product method to extend Sanchez's technique to decision problems related to prediction of stock market. The result shows that the new method provides more information about the decision of selling, buying or holding the position.